GMAT Prep (USA) States A-D Alabama Arizona Arkansas California Colorado Connecticut Delaware District of Columbia States F-L Florida Georgia Hawaii Illinois Indiana Iowa Kansas Kentucky Louisiana States M Massachusetts Maryland Michigan Minnesota Missouri Mississippi States N-O Nebraska Nevada New Jersey New York North Carolina Ohio Oklahoma Oregon States P-T Pennsylvania Rhode Island South Carolina Tennessee Texas States U-W Utah Vermont Virginia Washington Wisconsin West Virginia No Location? Online Courses GMAT Prep (International) Australia Canada China France Germany India Italy Japan Korea Mexico Norway Singapore Spain Sweden UAE United Kingdom No Location? Online Courses Favorite GMAT Articles Free GMAT Prep MBA Admissions Forums Forums Home GMAT Strategies and Content  Quantitative Reasoning Verbal Reasoning GMAT Strategies GMAT Essays MBA Admissions Discussions  MBA Admissions Help MBA Admissions Essays Commercial GMAT Preparation  800score Manhattan GMAT Veritas Contributors Manhattan GMAT Ron Purewal Stacey Koprince VeritasPrep Jim Stekelberg 800score Steve Alexandris GMAT MBA Prep JP Morgan

• Board contributors include instructors with "800" GMAT scores.
• 95% of posts have replies within 24 hours.
• Join for discounts with 800score, VeritasPrep and ManhattanGMAT

 FAQ  - Register  - Search - Login

 All times are UTC - 7 hours

 Page 1 of 1 [ 4 posts ]
 Print view Previous topic | Next topic
Author Message
 Post subject: GMAT Algebra (Data Sufficiency)Posted: Sat Jul 28, 2012 9:42 am

Joined: Tue Apr 13, 2010 8:48 am
Posts: 483
Is x > y ?
(1) x + 2√(xy) + y = 0
(2) x² – y² = 0

A. Statement (1) BY ITSELF is sufficient to answer the question, but statement (2) by itself is not.
B. Statement (2) BY ITSELF is sufficient to answer the question, but statement (1) by itself is not.
C. Statements (1) and (2) TAKEN TOGETHER are sufficient to answer the question, even though NEITHER statement BY ITSELF is sufficient.
D. Either statement BY ITSELF is sufficient to answer the question.
E. Statements (1) and (2) TAKEN TOGETHER are NOT sufficient to answer the question, meaning that further information would be needed to answer the question.

(A) Statement (1) has the term √(xy). So xy must be a non-negative number. It’s easy to see that if at least one of them is 0, then the other one must be 0 as well. If the both variables are positive, then the left side will be positive and it will NOT equal 0. If the both variables are negative then the equation transforms into
x + 2 × √(-x) × √(-y) + y = 0. Let’s multiply it by -1.
(-x) – 2√(-x)√(-y) + (-y) = 0. Note, that (-x) and (-y) are positive numbers. Let’s apply the formula of the sum of squares, where (-x) = (√(-x))² and (-y) = (√(-y))². This formula transforms the equation into
(√(-x) – √(-y))² = 0. This yields √(-x) = √(-y).
Therefore x = y, where x and y are NOT positive, is the solution of statement (1). Therefore we have the definite answer to the main question. Is x > y? NO. Statement (1) by itself is sufficient to answer the question.

Statement (2) transforms into x² = y². The solutions are
x = y
x = -y

As we already know, the first solution yields a definite answer NO to the main question. While the second solution can yield a positive answer to the main question. If y is negative (y = -1), then x is positive (x = +1) and so x > y (1 > -1). Statement (2) by itself is NOT sufficient to answer the question.

Statement (1) by itself is sufficient to answer the question, but statement (2) by itself is not. The correct answer is A.
----------
[color=#FF0000]Hi,

Can you please explain this in any alternative way?
I was not able to follow the explanation properly.

Thanks.[/color]

Top

 Post subject: Re: GMAT Algebra (Data Sufficiency)Posted: Sat Jul 28, 2012 10:06 am

Joined: Thu Jul 05, 2012 11:55 am
Posts: 64
[quote][color=#FF0000]Can you please explain this in any alternative way?[/color]
Statement (2) is quite simple, so let's deal with it first.
x² – y² = 0
x² = y²
|x| = |y|
This yields the two possible variants: x = y and x = -y .

Plug in a positive value for y into x = -y.
If y = 1, then x = -1 and "x > y" becomes -1 > 1 ,which is NOT true.

Plug in a negative value for y into x = -y.
If y = -1, then x = 1 and "x > y" becomes 1 > -1 ,which IS true.

Thus we have no definite answer for the question "Is x > y ?". Statement (2) by itself is NOT sufficient.

Statement (1) is much harder.
x + 2√(xy) + y = 0

If we had x + 2(√x)(√y) + y = 0 then we could easily turn it into
a² + 2ab + b², where a = √x and b =√y.
Think about it. Feel the difference with Statement (1). It is the key moment here.

But we have √(xy). The case x = 0 and y = 0 is obvious so I skip it. xy must be positive. So either the two numbers are both positive or both negative.
In other words √(xy) turns into √(x)√(y) if x and y are positive, and √(-x)√(-y) if x and y are negative.

If x and y are both positive then we have
positive + positive + positive = 0, which is impossible.

The only case is x and y are negative
x + 2(√-x)(√-y) + y = 0
Multiply by (-1) and it turns into
a² – 2ab + b² = 0, where a = √-x and b = √-y.
(ab)² = 0
a = b
√-x = √-y
-x = -y
x = y

And they both are non-positive numbers, but it is not important here. We know that x = y, so the definite answer to the question "Is x > y ?" is "NO".

Top

 Post subject: Re: GMAT Algebra (Data Sufficiency)Posted: Mon Aug 27, 2012 7:42 am

Joined: Tue Apr 13, 2010 8:48 am
Posts: 483
[color=#FF0000]One thing which I don't understand is that how can we take the X and Y numbers to be negative - for the statement 1, because (√x + √y)² = 0 can not happen for the X and Y to be negative they have to be the same.[/color]

Top

 Post subject: Re: GMAT Algebra (Data Sufficiency)Posted: Mon Aug 27, 2012 7:50 am

Joined: Thu Jul 05, 2012 11:55 am
Posts: 64
[quote="questioner"][color=#FF0000]One thing which I don't understand is that how can we take the X and Y numbers to be negative - for the statement 1, because (√x + √y)² = 0 can not happen for the X and Y to be negative they have to be the same.[/color]
(√x + √y)² = 0 ONLY if x = y = 0 . But (√x + √y)² = 0 is NOT statement (1). Statement (1) is
x + 2√(xy) + y = 0

while the proposed expression, (√x + √y)² = 0, is
x + 2(√x)(√y) + y = 0

Statement (1) implies that xy must be non-negative, while the proposed statement implies that x and y must be non-negative. Try to feel the difference.

Top

 Display posts from previous: All posts1 day7 days2 weeks1 month3 months6 months1 year Sort by AuthorPost timeSubject AscendingDescending
 Page 1 of 1 [ 4 posts ]

 All times are UTC - 7 hours

#### Who is online

Users browsing this forum: No registered users and 1 guest

 You cannot post new topics in this forumYou cannot reply to topics in this forumYou cannot edit your posts in this forumYou cannot delete your posts in this forumYou cannot post attachments in this forum

Search for:
 Jump to:  Select a forum ------------------ GMAT Strategies and Content    Quantitative Reasoning       Data Sufficiency       Problem Solving    Verbal Reasoning       Sentence Correction       Critical Reasoning       Reading Comprehension    GMAT Integrated Reasoning    GMAT Strategies    GMAT Essays    Videos MBA Admissions Discussions    MBA Admissions Help    MBA Admissions Essays Commercial GMAT Preparation    800score    Manhattan GMAT    Veritas    GMAT MBA Prep Members Only